Finding Interest Factor of Sharia Home Ownership Credit in Malang City - Saputra, Rangga (Maliki Islamic Economics Journal, 2024)
This study aims to identify factors influencing customer interest in Sharia Home Ownership Credit (KPRS) in Malang City. The study was conducted on 384 customers from 12 Islamic banks in Malang City who have used KPRS for at least one year. The study employs Exploratory Factor Analysis (EFA) to determine the underlying factors shaping customer interest in KPRS. The analysis revealed seven key factors: Service Quality (including officer performance and information delivery), Price (covering affordability and fees), Brand Image (encompassing professional impression and market coverage), Buying Interest (related to usury-free margins), Digital Media (involving information accessibility), Needs (focusing on product suitability), and Usefulness (including price-benefit alignment). The findings suggest that Islamic banks should enhance their digital presence, maintain competitive pricing, and ensure high service quality to improve their Sharia mortgage products. However, this study is limited by its geographical scope being restricted to Malang City, its focus only on existing customers rather than potential ones, and its timing during post-pandemic recovery, which may have influenced customer perspectives.